SIMULATION USING REGRESSION ANALYSIS OF MIDDLE CRANIAL FOSSA IN BOYS AND GIRLS OF VARIOUS CRANIOTYPES - Гунас, І.В.; Бабич, Л.В.; Черкасов, Е.В. (World of Medicine and Biology, 2017)
Aim of our work – to construct and analyze the regression models of individual computer-tomographic sizes of the middle cranial fossa (MCF) in practically healthy young men and girls of different craniotypes depending on the peculiarities of the structure and size of the body. Materials and methods Among aimed at doctors for CT-examination (examination regulations correspond to the MOH order of Ukraine by 04.06.2007 № 294 «On approval of the State sanitary rules and norms» "Hygienic requirements to placement and operation of X-ray rooms and radiology procedures") youths aged from 17 to 21 years and girls aged from 16 to 20 years in the third generation residents of Podillia region of Ukraine with suspected brain disease in which the diagnosis was not confirmed, additional test after screening assessment of health (using a special questionnaire) 82 healthy young men and 86 girls were selected. Computed tomographic examination of the brain was performed using the electron scanner "Select SP" of the ELscint company. Sections (thickness 5-10 mm) in axial projection performed in parallel to the upper orbit-meatal line pre-determining the level of scanning the overview scan of the skull in lateral projection. Linear dimensions (longitudinal and transverse) of the right and left MCF were determined at the levels of the tomograms T1 and T2. Anthropometric survey of boys and girls was conducted according to the scheme of Bunak in the modification of Shaparenko. Features of the form of the skull were calculated using a cranial pointer (the ratio of maximum head width to maximum head length). Given the distribution of boys and girls on different craniotypes (among boys - 12 dolichocephalic, 17 mesocephalic and 53 brachycephalic; and among girls - dolichocephalic 25, 38 mesocephalic and 23 brachycephalic) for regression modeling was not adolescent dolichocephalic. To evaluate the somatotype, a mathematical scheme for Hit-Carter was used. By formulas of J. Matiegka determined the fat, bone and muscle mass components of the body. In addition, by the American Institute of Nutrition, the muscle component of the body mass was determined. To develop individual models computed tomographic sizes of MCF depending on the characteristics and anthropometric indicators in somatic license package "STATISTICA 6.1" method used stepwise regression analysis. Results. Discussions It was established that from 6 possible computer-tomographic dimensions of MCF in mesocephalic males, depending on the characteristics of anthropometric and somatotypological indicators, all 6 of which the determination coefficient (R2) was from 0.855 to 0.955 were constructed. The models often include cephalometric parameters (32.3%), diameters and girths of body (19.4%). In brachycephalic youths, for all 6 possible computational-tomographic sizes of MCF, depending on the features of the anthropometric and somatotypological indicators R2 in the models ranged from 0.611 to 0.802. The built models often include cephalometric indices and girths of the body (by 25.7%), as well as the thickness of skin and fat folds (17.1%). In girls dolichocephalic for all 6 possible computer-tomographic sizes of MCF depending on the features of anthropometric and somatotypological indicators of R2 in models ranged from 0.705 to 0.900. The built models often include cephalometric indices and width of distal epiphyses of long limb bones (22.9%) and body length girths (20.0%). In girls-mesocephals from 6 possible computer-tomographic sizes of MCF depending on the features of anthropometric and somatotypological indicators, 3 models were constructed in which R2 was from 0.665 to 0.719. The built models often include cephalometric indices (42.9%). In brachycephalic girls from 6 possible computer-tomographic sizes of MCF, depending on the features of anthropometric and somatotypological indicators, constructed 4 models in which R2 ranged from 0.811 to 0.866. The built models most often include circumferential body dimensions (28.0%), cephalometric indices and thickness of skin and fat folds (by 16.0%).